On the computation of hybrid modes in planar layered waveguides with multiple anisotropic conductive sheets. (31st October 2018) - Michalski, K. A.; Mustafa, M. M.
Abstract : A reliable method is presented for the computation of the propagation constants and the corresponding hybrid modal fields in multilayered planar dielectric stacks comprising multiple anisotropic conducting sheets. The appropriate dispersion functions (DFs) are formulated and evaluated using a numerically stable scattering matrix methodology. The roots of the DFs are computed by the Cauchy integration method with automatic differentiation of the DF.